2018
DOI: 10.1371/journal.pone.0196731
|View full text |Cite
|
Sign up to set email alerts
|

Seabird bycatch mitigation trials in artisanal demersal longliners of the Western Mediterranean

Abstract: High numbers of seabirds are killed annually worldwide in longline fisheries. In the Mediterranean, this mortality is seriously affecting the viability of seabird populations, in particular of the three endemic shearwaters. Even so, there is currently no specific seabird mitigation requirements for the longline fleet operating in this area. From 2013 to 2014, we assessed the efficiency and practical applicability of four mitigation measures on artisanal demersal longliners targeting European hake (Merluccius m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Several approaches have been tested around the world to reduce seabird bycatch in longlines. Night setting showed a greater potential to reduce seabird bycatch in small scale fisheries operating in the Western Mediterranean when compared to tori lines, weighted lines or artificial bait (Cortés and González-Solís 2018). In our case, seabird bycatch occurred while longlines were soaked in the water, preventing the successful use of tori lines or other devices, like underwater setting and line shooters installed in the fishing boats and tested by Løkkeborg (2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches have been tested around the world to reduce seabird bycatch in longlines. Night setting showed a greater potential to reduce seabird bycatch in small scale fisheries operating in the Western Mediterranean when compared to tori lines, weighted lines or artificial bait (Cortés and González-Solís 2018). In our case, seabird bycatch occurred while longlines were soaked in the water, preventing the successful use of tori lines or other devices, like underwater setting and line shooters installed in the fishing boats and tested by Løkkeborg (2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at a global level, gaps in knowledge of seabird bycatch are more noted in areas where small-scale fisheries are more prevalent. Nevertheless, seabird bycatch has already been reported for some regions, namely the Pacific (Melly et al 2006, Moreno et al 2006), Atlantic (Bugoni et al 2008, Shester and Micheli 2011) and Mediterranean (Cooper et al 2003, Cortés et al 2017, Cortés and González-Solís 2018). The main constraints on collecting bycatch data from artisanal fisheries are related to the limitations on accommodating observers on such small-sized vessels.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, a switch from current 3kg to 5kg weights for a set of ten thousand hooks would represent roughly an additional half a tonne to be carried onboard and handled by fishers. Cortés & González-Solís [ 51 ] also found that in artisanal demersal longlines, more weight is susceptible to increase entanglement risks between the branchlines and hooks during the setting operations. However, change in the longline weighting regime is the single measure most likely to deliver a significant reduction in seabird bycatch, and a series of measures that could help reduce operational issues should be investigated such as alternative spacing between branchlines and between weights [ 52 ], use of steel weights instead of concrete [ 29 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Several simple and effective seabird bycatch mitigation measures for longline fisheries already exist [ 6 ] but most have been developed and tested in the southern hemisphere longline fisheries [ 7 10 ]. To date, limited work has been conducted to test, adapt or implement these measures for the unique set of challenges posed by ‘floated’ demersal longlines (also referred to as ‘ Spanish longline’ [ 11 ], ‘ piedra bola’ [ 12 ] or ‘semi-pelagic longline’ [ 13 ]), which are predominantly used in the North-East Atlantic to target Hake and other whitefish fisheries. This fishery operates mainly in the ecoregion known as the Celtic Seas (ranging from the north of the Shetland Islands to Brittany in the south [ 14 ]) and towards the Bay of Biscay, including the area referred to as the ‘ Gran Sol ’ [ 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several simple and effective seabird bycatch mitigation measures for longline fisheries already exist [6] but most have been developed and tested in the southern hemisphere longline fisheries [7][8][9][10]. To date, limited work has been conducted to test, adapt or implement these measures for the unique set of challenges posed by 'floated' demersal longlines (also referred to as 'Spanish longline' [11], 'piedra bola' [12] or 'semi-pelagic longline' [13]), which are predominantly used in the North-East Atlantic to target Hake and other whitefish fisheries. This fishery operates mainly in the ecoregion known as the Celtic Seas (ranging from the north of the Shetland Islands to Brittany in the south [14]) and towards the Bay of Biscay, including the area referred to as the 'Gran Sol' [3,15].…”
Section: Introductionmentioning
confidence: 99%